Successful Treatment of Secondary Aortoenteric Fistula with a Special Graft - Ömer Faruk Çiçek; Mustafa Cüneyt Çiçek; Ersin Kadiroğulları; Alper Uzun; Mahmut Ulaş (Case Reports in Medicine)
Aortoenteric fistula is an uncommon but life-threatening cause of gastrointestinal blood loss. We report a case of a 70-year-old man who presented to the emergency department with an episode of melena and infection in the left inguinal region. Diagnosis of secondary aortoenteric fistula was made between the left limb of the aortobifemoral graft and the descending colon. We performed excision of the infected graft and in situ silver acetate coating of prosthetic vascular graft replacement (aortoleft femoral) on the patient. This study reports a rare type of secondary aortoenteric fistula to the left colon, and it describes an unusual and successful surgical treatment. Antimicrobial coating of prosthetic vascular grafts may be a good alternative in the presence of graft infection associated with aortoenteric fistula because in situ grafts may carry an increased risk of reinfection.